Manajemen dan Administrasi Keuangan MTs Muhammadiyah 3 Al-Furqon - Bayu Tri Lenggono; Muhammad Rudy Rosehan; Muhammad Miqdad; Muhammad Afdil Hermawan; Suhaimi Suhaimi (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Financial management and administration have an important role in maintaining the sustainability and quality of educational institutions. Effective financial management is one of the indicators of good institutional governance and has a direct effect on the quality of educational services. This study aims to analyze the implementation of financial management and administration in MTs Muhammadiyah 3 Al-Furqon Banjarmasin. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, direct observations, and documentation studies. The results of the study show that the financial management of madrasah has been carried out systematically and transparently with a clear division of duties between the head of the madrasah, the treasurer, and the school committee. The use of the Madrasah Activity Plan and Budget (RKAM) digital application has been proven to increase efficiency, accuracy, and administrative order in financial reporting. However, there are still several obstacles, such as delays in the disbursement of School Operational Assistance (BOS) funds and limited internet networks. Good cooperation between madrassas and foundations also plays a role in maintaining the sustainability of educational programs. Overall, the madrasah financial system reflects the principles of transparency, accountability, and professionalism in the management of education finances.